희첨류 한약재의 포제가 혈압에 미치는 영향 - 최동일; Dong Il Choi; 함인혜; In Hye Ham; 박규하; Kyu Ha Park; 최호영; Ho Young Choi (대한본초학회지(본초분과학회지), 2005)
Objective : This study was carried out to compare the components regarding medicinal parts of Siegesbeckiae Herba and its habitats using TLC patterns. Then hypotentive effects, which depend on the preparation process was measured on Siegesbeckiae Herba. Methods : The Siegesbeckiae Herba were prepared with 70% MeOH extract and was fractionized. Also Siegesbeckiae Herba was steamed several times with Makkolli and its residue was attained. Hypotensive effect was obtained by measuring mean B.P. from femoral artery in rats. Results : The components were significantly different depending on their medicinal parts and habitats in TLC patterns. The more Siegesbeckiae Herba was steamed, the more some compounds decreased. As for mean B.P., it dropped significantly when Siegesbeckiae Herba was steamed 9 times. It dropped remarkably after 30 min. then mainteined afterwards. Also 60% and 100% methanol fraction of Siegesbeckiae Herba showed significant hypotensive effect. Conclusions : We concluded that Siegesbeckiae Herba have different compounds according to their medicinal parts and habitats. Also the steaming process with Makkolli increases hypotensive activity.